Effect of dietary inclusion of spray‐dried porcine plasma on performance, some physiological and immunological response of broiler chickens challenged with Salmonella sofia. Issue 5 (28th November 2015) - Beski, S. S. M.; Swick, R. A.; Iji, P. A.
Summary: This study was conducted to investigate the effect of spray‐dried porcine plasma (SDPP) in broiler chickens under Salmonella sofia disease challenge. The experiment comprised five starter diets: positive control (no supplement), diet supplemented with in‐feed antibiotics (IFA; salinomycin 0.05% + zinc bacitracin 0.033%) and diets supplemented with SDPP at 10 or 20 g/kg diet. All four of these groups were challenged with S .  sofia, while a fifth group was unchallenged and used as the negative control. The experimental diets were fed to 14 days; then, the birds were switched to commercial‐type grower and finisher diets. Oral inoculation of the challenged groups with S .  sofia occurred on day 8, 10 and 12. Body weight was significantly higher in the birds fed diets containing IFA and SDPP than in the challenged control group, but it was only significant in starter and grower phases. In general, there was an improvement in the weights of the immune‐related organs, but it was only significant for the weight of the bursa of SDPP‐fed birds at 13 days. At day 13, blood potassium content was lower and the concentrations of IgG and IgM tended to be lower in the birds fed on low‐SDPP starter diets than those of the other groups. There were significant differences in the concentration of lactic acid in the ileum and acetic acid, formic acid, butyric acid and propionic acid in the caeca. Inclusion of SDPP to the starter diets of broiler chicks had positive effects on broiler performance, immunity and gut health during exposure to highly pathogenic conditions.